Demand driven documentation in Open Source projects - Can Demand driven documentation work as a substitute for regular documentation in Open source projects? - Andersson, Jessica; Larsson, Sofia (My University, 2014)
This case study researches how demand driven documentation can be exploited by Open Source projects. The study has been conducted on documentation created on the Q&A site StackOver ow, with in-depth research of the two Open Source projects Apache POI and Firefox for Android. The reader will nd that documentation provided by the community is in general of good quality and often provided within an acceptable amount of time. One will as well nd how projects of di erent nature can exploit demand driven documentation in di erent ways. Finally the authors concluded that demand driven documentation could be suitable as a primary resource for information if it is accompanied by other forms of resources. However, the suitability is closely related to the size and activeness of the project's community
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology